Switching from tenofovir disoproxil fumarate to tenofovir alafenamide in antiretroviral regimens for virologically suppressed adults with HIV-1 infection: a randomised, active-controlled, multicentre, open-label, phase 3, non-inferiority study. Issue 1 (January 2016) - Mills, Anthony; Arribas, Jose R; Andrade-Villanueva, Jaime; DiPerri, Giovanni; Van Lunzen, Jan; Koenig, Ellen; Elion, Richard; Cavassini, Matthias; Madruga, Jose Valdez; Brunetta, Jason; Shamblaw, David; DeJesus, Edwin; et al.
Summary: Background: Antiretroviral regimens containing tenofovir disoproxil fumarate have been associated with renal toxicity and reduced bone mineral density. Tenofovir alafenamide is a novel tenofovir prodrug that reduces tenofovir plasma concentrations by 90%, thereby decreasing off-target side-effects. We aimed to assess whether efficacy, safety, and tolerability were non-inferior in patients switched to a regimen containing tenofovir alafenamide versus in those remaining on one containing tenofovir disoproxil fumarate. Methods: In this randomised, actively controlled, multicentre, open-label, non-inferiority trial, we recruited HIV-1-infected adults from Gilead clinical studies at 168 sites in 19 countries. Patients were virologically suppressed (HIV-1 RNA <50 copies per mL) with an estimated glomerular filtration rate of 50 mL per min or greater, and were taking one of four tenofovir disoproxil fumarate-containing regimens for at least 96 weeks before enrolment. With use of a third-party computer-generated sequence, patients were randomly assigned (2:1) to receive a once-a-day single-tablet containing elvitegravir 150 mg, cobicistat 150 mg, emtricitabine 200 mg, and tenofovir alafenamide 10 mg (tenofovir alafenamide group) or to carry on taking one of four previous tenofovir disoproxil fumarate-containing regimens (tenofovir disoproxil fumarate group) for 96 weeks. Randomisation was stratified by previous treatment regimen in blocks of six. Patients and treating physicians were not masked to the assigned study regimen; outcome assessors were masked until database lock. The primary endpoint was the proportion of patients who received at least one dose of study drug who had undetectable viral load (HIV-1 RNA <50 copies per mL) at week 48. The non-inferiority margin was 12%. This study was registered withClinicalTrials.gov, numberNCT01815736 . Findings: Between April 12, 2013 and April 3, 2014, we enrolled 1443 patients. 959 patients were randomly assigned to the tenofovir alafenamide group and 477 to the tenofovir disoproxil fumarate group. Viral suppression at week 48 was noted in 932 (97%) patients assigned to the tenofovir alafenamide group and in 444 (93%) assigned to the tenofovir disoproxil fumarate group (adjusted difference 4·1%, 95% CI 1·6–6·7), with virological failure noted in ten and six patients, respectively. The number of adverse events was similar between the two groups, but study drug-related adverse events were more common in the tenofovir alafenamide group (204 patients [21%] vs 76 [16%]). Hip and spine bone mineral density and glomerular filtration were each significantly improved in patients in the tenofovir alafenamide group compared with those in the tenofovir disoproxil fumarate group. Interpretation: Switching to a tenofovir alafenamide-containing regimen from one containing tenofovir disoproxil fumarate was non-inferior for maintenance of viral suppression and led to improved bone mineral density and renal function. Longer term follow-up is needed to better understand the clinical impact of these changes. Funding: Gilead Sciences.